Complete excision of a large pancreatic neuroendocrine neoplasm - Darko, R.; Edwin, F.; Anim, J. (Pan African Medical Journal, 2018)
Pancreatic neuroendocrine tumours localized to the pancreas and amenable to complete surgical resection are rarely reported. In West Africa, such patients present too late for surgery to be considered. In the reported case, a patient with persistent epigastric pain underwent a computed tomographic examination which led to the discovery of a large (6cm x 5cm) localized tumour in the body and tail of the pancreas. Complete resection of the tumour was performed. Histological examination showed a pancreatic neuroendocrine tumour without capsular invasion. Adjuvant chemotherapy was deemed unnecessary. The patient remains symptom free 2 years after the procedure with no evidence on subsequent imaging of tumour recurrence. Although extremely rare, large pancreatic neuroendocrine tumours may still be amenable to complete excision.
Keywords: Pancreas; Neuroendocrine; Carcinoma; Synaptophysin